The impact of market concentration on competitivness of the banking sector in Serbia - Đuranović, Gordana; Filipović, Sanja (Industrija, 2022)
The concentration level is proof of development and tendencies on the observed market. It determines the existence of competition and fair play among competitors and participants. This paper aims to analyse and measure the concentration level within the banking sector in the Republic of Serbia. The concentration level is measured applying the concentration ratio for four and five biggest banks (Cr4 and Cr5) and Herfindal-Hirschman index (HH index) in the period from 2018 to the third quarter of 2020 for the following banks’ balance sheet positions: assets, approved loans, and collected deposits. The banking market is reported to be medium concentrated according to CR5 and low concentrated according to Cr4 and HHI in all observed categories. The empirical research shows that there is competition among banks in Serbia (loose oligopoly), which depends on the concentration level